Frequency of alpha oscillation predicts individual differences in perceptual stability during binocular rivalry - Katyal, Sucharit (Hum Brain Mapp, 2019)
When ambiguous visual stimuli have multiple interpretations, human perception can alternate between them, producing perceptual multistability. There is a large variation between individuals in how long stable percepts endure, on average, between switches, but the underlying neural basis of this individual difference in perceptual dynamics remains obscure. Here, we show that in one widely studied multistable paradigm–binocular rivalry–perceptual stability in individuals is predicted by the frequency of their neural oscillations within the alpha range (7–13 Hz). Our results suggest revising models of rivalry to incorporate effects of neural oscillations on perceptual alternations, and raise the possibility that a common factor may influence dynamics in many neural processes.